2005
DOI: 10.1111/j.1365-294x.2005.02646.x
|View full text |Cite
|
Sign up to set email alerts
|

Genomic organization of molecular differentiation in Norway spruce (Picea abies)

Abstract: Diversity and differentiation among three populations representing the geographical domains commonly recognized within the natural distribution area of Picea abies were analysed by using a set of 292 AFLP (amplified fragment length polymorphism), SSR (single sequence repeat) and ESTP (expressed sequence tags polymorphism) markers. As usually observed in forest trees, results showed high within-population diversity (H(S) reaching 0.79) and low among-population differentiation (G(ST) approximately 2%). The genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
66
3
5

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 59 publications
9
66
3
5
Order By: Relevance
“…As shown previously with other molecular markers [allozymes (Lagercrantz and Ryman 1990), AFLP (Acheré et al 2005), and cytoplasmic DNA Sperisen et al 2001)], the Norway spruce population is today genetically and geographically divided into two main domains, namely the Baltico-Nordic domain and the Alpine Central European domain, and a more limited one, the Carpathian domain, represented in the present survey by a single population, Romania. This population had a very limited polymorphism and may not be representative of the Carpathian domain.…”
Section: Discussionsupporting
confidence: 76%
“…As shown previously with other molecular markers [allozymes (Lagercrantz and Ryman 1990), AFLP (Acheré et al 2005), and cytoplasmic DNA Sperisen et al 2001)], the Norway spruce population is today genetically and geographically divided into two main domains, namely the Baltico-Nordic domain and the Alpine Central European domain, and a more limited one, the Carpathian domain, represented in the present survey by a single population, Romania. This population had a very limited polymorphism and may not be representative of the Carpathian domain.…”
Section: Discussionsupporting
confidence: 76%
“…The identification of genes related to local adaptation and differentiation is also essential for the conservation of local populations. However, such genes have only been identified in model plants to date (for a review, see Shimizu and Purugganan, 2005), although genomic regions associated with speciation and population differentiation have been reported in several forest tree species, including Quercus and Picea abies (Scotti-Saintagne et al, 2004;Acheré et al, 2005). Thus, there is an urgent need to extend the identification of such genes to the genomes of other species to facilitate conservation efforts.…”
Section: Introductionmentioning
confidence: 99%
“…The number of alleles per locus obtained in this research is lower than those described by other authors for P. abies. Acheré et al (2005) found alleles per locus for the 25 microsatellites studied in the range of 5-55 (25 in average). Maghuly et al (2006) detected 27 (in average) alleles within five loci.…”
Section: Genetic Variablesmentioning
confidence: 91%
“…Individual samples from each of the six locations are dispersed throughout the entire dendrogram because of the large intrapopulation variability. Several studies have shown that genetic variation is relatively high and that the majority is partitioned within (rather than between) populations (Cottrell et al 2003;Acheré et al 2005). Maghuly et al (2006) analyzed genetic diversity in different subpopulations of Norway spruce in Austria by nuclear SSRs finding more genetic variation and heterozygosity within populations than among populations.…”
Section: Locus Eac1d10mentioning
confidence: 99%
See 1 more Smart Citation